A THEATRİCAL VİLLAGE PLAY FROM AFYONKARAHİSAR REGİON: “CAMELEER PLAY” - Yigit, Neslihan Huri (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The theatrical village play which is formed through the examination of the tradition, culture, and ways of living of the Anatolian people, still exists in several villages. When these plays are sociologically analysed, the past and lives of Anatolian village would be demonstrated. In this study we will shortly define the theatrical village play and the "Cameleer Play" which is played and presented in Afyonkarahisar.